Assessing Corticospinal Tract Asymmetry in Unilateral Polymicrogyria - Foesleitner, O. (AJNR Am J Neuroradiol, 2018)
BACKGROUND AND PURPOSE: Asymmetry of the corticospinal tract in congenital lesions is a good prognostic marker for preserved motor function after hemispherectomy. This study aimed to assess this marker and provide a clinically feasible approach in selected cases of unilateral polymicrogyria. MATERIALS AND METHODS: Corticospinal tract asymmetry of 9 patients with unilateral polymicrogyria substantially affecting the central region was retrospectively assessed on axial T1WI and DTI. Volumes of the brain stem and thalamus and DTI parameters of the internal capsule were measured. Two neuroradiologists independently rated the right-left asymmetry at 4 levels along the corticospinal tract. DTI tractography was used to determine the motor cortex within polymicrogyria, with task-based functional MR imaging available in 3/9 cases. RESULTS: Visual assessment of the brain stem asymmetry showed excellent correlation with quantitative measures on both T1WI and color-coded DTI maps (P = .007 and P = .023). Interrater reliability regarding structural and DTI-based corticospinal tract asymmetry was best at the midbrain (Cohen κ = 0.77, P = .018). Three patients underwent functional hemispherectomy with postsurgical stable motor function, all showing marked corticospinal tract asymmetry preoperatively. Following the DTI-based corticospinal tract trajectories allowed identifying the presumed primary motor region within the dysplastic cortex in 9/9 patients, confirmed by functional MR imaging in 3/3 cases. CONCLUSIONS: Visual assessment of corticospinal tract asymmetry in unilateral polymicrogyria involving the motor cortex is most reliable with T1WI and color-coded DTI maps at the level of the midbrain. Pronounced asymmetry predicts preserved motor function after hemispherectomy. DTI-based tractography can be used as a guidance tool to the motor cortex within polymicrogyria.